Which Scoring System is Better in Predicting Mortality in Multiple Trauma Patients: Revised Trauma Score or Glasgow Coma Scale - Adem Az; Çiğdem Orhan (Global Emergency and Critical Care)
Objective: We investigated the prognostic value of the revised trauma score (RTS) and Glasgow Coma scale (GCS) in predicting mortality in multitrauma patients. Materials and Methods: This retrospective study included 537 consecutive trauma patients with a shock index ≥1.0. We evaluated the demographics, clinical characteristics, and trauma scores, including GCS and RTS, in both the survivor and non-survivor groups. Results: A total of 537 patients, comprising 58.29% males and 41.71% females, with a mean age of 44.46±22.05 years, were included. Overall mortality was 13.04%. Age and sex differed significantly between survivors and non-survivors (p=0.0001 and p=0.001). Non-survivors had significantly lower mean GCS and RTS scores (p=0.0001 for both comparisons). Receiver operating characteristic analysis identified a GCS ≤10 for predicting mortality in multi-trauma patients, with 99.89% sensitivity and 99.79% specificity. Additionally, an RTS ≤8 had 98.57% sensitivity and 99.79% specificity for determining mortality. Conclusion: Our results indicated that lower mean GCS and RTS scores were predictors of mortality in multi-trauma patients. A GCS of ≤10 and an RTS of ≤8 exhibited exceptional sensitivity and specificity for determining mortality in multi-trauma patients.